In silico structure evaluation of BAG3 and elucidating its association with bacterial infections through protein–protein and host‐pathogen interaction analysis. Issue 1 (17th May 2021) - Basu, Soumya; Naha, Aniket; Veeraraghavan, Balaji; Ramaiah, Sudha; Anbarasu, Anand
Abstract: BAG3, a co‐chaperone protein with a Bcl‐2‐associated athanogene (BAG) domain, has diverse functionalities in protein‐folding, apoptosis, inflammation, and cell cycle regulatory cross‐talks. It has been well characterised in cardiac diseases, cancers, and viral pathogenesis. The multiple roles of BAG3 are attributed to its functional regions like BAG, Tryptophan‐rich (WW), isoleucine‐proline‐valine‐rich (IPV), and proline‐rich (PXXP) domains. However, to study its structural impact on various functions, the experimental 3D structure of BAG3 protein was not available. Hence, the structure was predicted through in silico modelling and validated through computational tools and molecular dynamics simulation studies. To the best of our knowledge, the role of BAG3 in bacterial infections is not explicitly reported. We attempted to study them through an in‐silico protein–protein interaction network and host‐pathogen interaction analysis. From structure‐function relationships, it was identified that the WW and PXXP domains were associated with cellular cytoskeleton rearrangement and adhesion‐mediated response, which might be involved in BAG3‐related intracellular bacterial proliferation. From functional enrichment analysis, Gene Ontology terms and topological matrices, 18 host proteins and 29 pathogen proteins were identified in the BAG3 interactome pertaining to Legionellosis, Tuberculosis, Salmonellosis, Shigellosis, and Pertussis through differential phosphorylation events associated with serine metabolism. Furthermore, it was evident that direct (MAPK8, MAPK14) and associated (MAPK1, HSPD1, NFKBIA, TLR2, RHOA) interactors of BAG3 could be considered as therapeutic markers to curb down intracellular bacterial propagation in humans. Abstract : The co‐chaperone protein BAG3 is involved directly or indirectly in bacterial pathogenesis. BAG3 directly interacts with bacterial SerA protein, which is known to involve in L‐serine biosynthesis in bacteria, especially in Mycobacterium tuberculosis . Other bacterial intervening pathways communicate with a total of 18 host proteins through an array of interactions governed by BAG3 and its direct interactors HSPA1A, HSP90AA1, MAPK8,  and MAPK14. The involvement of BAG3 in Tuberculosis, Legionellosis, Salmonellosis, Shigellosis, and Pertussis established crucial roles of BAG3 in stress‐related cellular processes